DETERMINATION OF FLAVONOIDS IN THE FRUIT PERICARP OF HORSE CHEST-NUT (AESCULUS HIPPOCASTANUM L.) (Scientific journal of the Fergana State University, 2026)
In recent decades, medicinal plants have garnered significant scientific attention as natural alternatives to synthetic pharmaceuticals due to their low toxicity, high efficacy, and minimal side effects. Among these, horse chestnut (Aesculus hippocastanum L.) is one of the most widely used medicinal plants in both traditional medicine and modern pharmaceutical formulations. Horse chestnut is well known for its content of biologically active compounds, including esculin, escin, aescin, and a diverse range of flavonoids. These compounds have demonstrated considerable potential in the treatment of vascular diseases. Flavonoids, in particular, are recognized for their potent venotonic, anti-inflammatory, and antioxidant activities. Their use is widespread in the treatment of chronic venous insufficiency, varicose veins, hemorrhoids, and thrombophlebitis. Numerous studies have confirmed that horse chestnut extracts can enhance blood circulation, strengthen capillary walls, and effectively reduce swelling and inflammation.